Hamid Fahmy Zarkasyi’ Critics Toward Liberalism - Jefry Anggara; Mohammad Izdiyan Muttaqin (Islamika Granada, 2024)
The evolution of Islamic thought in Indonesia has been shaped by social, political, and economic changes, with a central theme being the critique of liberalism. Liberalism, emphasizing individualism, freedom, and tolerance, has permeated various societal aspects, including religious understanding, social structures, and political policies. Amidst this, influential figures like Hamid Fahmy Zarkasyi have emerged as notable critics. This article examines Zarkasyi's critiques of liberalism, highlighting his concerns about the dilution of Islamic values due to external influences. Employing qualitative research within an interpretive paradigm, the study analyzes Zarkasyi's writings and relevant secondary sources through descriptive-analytical methods. Findings reveal Zarkasyi's argument that liberalism's focus on absolute individual freedom undermines moral and social responsibilities central to Islam. He views liberalism as a potential threat to Islamic identity and cultural values, advocating for a balance between individual rights and collective ethical principles. Zarkasyi's intellectual contributions offer a critical framework for assessing liberalism's impact on Islamic thought in Indonesia, providing insights into maintaining authentic Islamic values amidst global influences.